Prototype star fruit-honey product and effectiveness on antixidants, inflammation and walking distance in participants with stable chronic obstructive pulmonary disease (COPD) - Yothin Pothasak (2020)
© 2020 Phcogj.Com. This is an open-access article distributed under the terms of the Creative Commons Attribution 4.0 International license. Background: Star fruit (Averrhoa carambola L.) is a seasonal fruit, which has proven antioxidant and inflammation activities in vitro. However, sweet-type is more available than sour-type. Therefore, developing a new product from sweet-type star fruit, and evaluating its effectiveness on antioxidants and inflammation have been very challenging. Objectives: The aims were to develop a prototype product from sweet-type star fruit and evaluate its effectiveness with or without walking exercise on participants with stable chronic obstructive pulmonary disease (COPD). Methods: The prototype product of sweet-type star fruit was prepared industrially by mixing with honey before nutrients such as L-ascorbic acid (Vit C) and total phenolic compound, and contaminants like chemicals, microbials and oxalic acid were evaluated. Effectiveness of this product on antioxidents, inflammation and physical function was evaluated in participants with stable COPD with and without walking exercise, and compared to walking exercise and control participants. Two spoons of the product (20 g) in sterile warm water (150 mL) were guided and consumed twice daily for 4 weeks, whereas the walking exercise was prescribed with moderate intensity at home for 30 min 3 days per week. Plasma Vit C, total antioxidant capacity (TAC), malondialdehyde (MDA), tumor necrotic factor-alpha (TNF-∝) and 6-minutes walking distance (6MWD) were evaluated before and after the 4-week study period. Results: The prototype product composed of star fruit juice with honey (1:1, v:v). Main nutrients were composed of ash (0.4 g), carbohydrate (74.59 g), lipid (2.88 g), protein (0.57 g) and 326.56 kcal of total energy, whereas Vit C and total phenolic compound were equivalent to 0.25 ± 0.11 mg and 144.89 ± 2.51 µg gallic acid equivalent in a 100 gram of product. The results of chemicals and microbials showed safety under food conditions. The results of study compared the ages of stable COPD participants between those of the controls (n=10, 69.20±1.40 years), and those with star fruit juice and honey supplement (n=20, 71.25 ± 6.01 years), walking exercise (n=15, 60.60±3.38 years), and supplement with walking exercise (n=15, 64.40±1.63 years) and no statistical difference was shown in any parameters in the control group. Whereas, the plasma Vit C and TAC levels increased, and MDA and TNF-∝ levels reduced significantly, in the supplement consumption group, which was in contrast to the Vit C, MDA and TNF-∝ levels in the walking exercise group. However, the TAC level increased significantly when the walking exercise was completed. When the prototype product was applied to the walking exercise, the levels of Vit C and TAC increased, and MDA and TNF-∝ levels reduced significantly. Whereas, the supplement levels increased significantly in all of the groups, especially in the 6MWD. Conclusion: This study proposed that sweet-type star fruit can be prepared industrially by mixing with honey, and be developed as a new commercial product with antioxidant and inflammation activities for participants suffering with chronic lung disease.